International Trade Financing Through Leasing - Kheloui ,Abdallah Chekib; Bachounda, Rafik (جامعة الوادي University of Eloued, 2025)
A lease is the temporary acquisition of the right to use a property. Leasing is a financing technique in which the right to use an asset for all or almost all of its economic life is granted to the lessee for a certain price, and at the end of this period, the right of ownership of the asset is transferred. International leasing operations are the cross-border version of leasing transactions. International leasing operations in Algeria; It is shaped by leasing legislation, tax legislation, customs legislation, international law legislation and other legislation. Since international leasing operations are shaped by national laws and international conventions, it is necessary to comply with the standards developed for its accounting. The aim of this study is to provide information about international financial leasing, to examine it in terms of legal regulations and to examine the accounting process (in terms of financial leasing company). To this end, international leasing operations are examined theoretically, data on the international trade situation in Algeria are presented, examined in terms of legal legislation, and import applied (full import incentive certificate) and special cases are dealt with to deal with the accounting of leasing operations in international trade
International trade financing through leasing: a means of investment assistance in Algeria. Operations and Establishment
مقال
Keywords: leasing; financial leasing; financial leasing in international trade; Algerian financial accounting system; accounting